2011
DOI: 10.1039/c1ib00073j
|View full text |Cite
|
Sign up to set email alerts
|

Collective epithelial cell invasion overcomes mechanical barriers of collagenous extracellular matrix by a narrow tube-like geometry and MMP14-dependent local softening

Abstract: Collective cell invasion (CCI) through interstitial collagenous extracellular matrix (ECM) is crucial to the initial stages of branching morphogenesis, and a hallmark of tissue repair and dissemination of certain tumors. The collagenous ECM acts as a mechanical barrier against CCI. However, the physical nature of this barrier and how it is overcome by cells remains incompletely understood. To address these questions, we performed theoretical and experimental analysis of mammary epithelial branching morphogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 65 publications
(238 reference statements)
8
72
0
Order By: Relevance
“…Our data showing up-regulation of Mmp2, Mmp11, Mmp14, Lox, and Lox3 are consistent with a previous report on regulation of Mmp expression and collagen contraction by EGFR-ERK signaling in mouse embryonic fibroblasts (48). Importantly, several Mmps, including Mmp2, Mmp3, and Mmp14, have been shown to regulate mammary epithelial branching in vivo (49,50). Consistent with increased Mmp and Lox gene expression, we found that organized collagen deposition was higher in Spry1KO mammary glands than in Spry1het glands during development.…”
Section: Discussionsupporting
confidence: 81%
“…Our data showing up-regulation of Mmp2, Mmp11, Mmp14, Lox, and Lox3 are consistent with a previous report on regulation of Mmp expression and collagen contraction by EGFR-ERK signaling in mouse embryonic fibroblasts (48). Importantly, several Mmps, including Mmp2, Mmp3, and Mmp14, have been shown to regulate mammary epithelial branching in vivo (49,50). Consistent with increased Mmp and Lox gene expression, we found that organized collagen deposition was higher in Spry1KO mammary glands than in Spry1het glands during development.…”
Section: Discussionsupporting
confidence: 81%
“…All these findings strongly support that matrix stiffening alone may be as important as soluble growth factors in driving fibroblast accumulation in vivo, thereby challenging the current view of stromagenesis as driven by paracrine signaling only (3,(8)(9)(10). Moreover, they extend previous evidence of a positive feedback loop in which activated fibroblasts lay out increased amounts of fibrotic ECM components that render a stiffer ECM, which in turn may drive fibroblast activation and accumulation further (11,14).…”
Section: Discussionmentioning
confidence: 32%
“…First, increasing the rigidity of culture substrata enhances the effects of exogenous growth factors on the survival and/or proliferation of fibroblasts from nonmalignant tissues (11)(12)(13). Second, a marked increase in matrix rigidity is expected in the stroma of NSCLC, because two hallmarks of desmoplastic tumors-abundant collagen-I fibers and a-SMA þ fibroblastshave been associated with dramatic tissue hardening (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of the important ECM regulatory role in vivo has extended the use of three-dimensional (3D) cultures based on growing cells embedded in gels of native ECM components [1,2]. Thus, the availability of ECM macromolecules from major tissue types including type I collagen (COLI) and reconstituted basement membrane (rBM, also known as Matrigel or EHS matrix) has enabled using 3D cultures to study different cell types in a variety of physiopathological processes such as differentiation, morphogenesis and invasion [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%